2021
DOI: 10.17794/rgn.2021.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of the Discontinuity Direction on Fluid Flow in Porous Rock Masses on a Large-Scale Using Hybrid FVM-DFN and Streamline Simulation

Abstract: Understanding the fluid behaviour in rock masses is of great importance in various rock mass-related engineering projects, such as seepage in tunnels, geothermal reservoirs, and hazardous waste disposal. Different approaches have been implemented to study the flow pattern in fractured porous rock masses. Laboratory experiments can provide good information regarding this issue, but high expenses aside, they are time-consuming and suffer the lack of ability to study field scale mediums. Numerical methods are ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Faez et al [16] studied the effect of fracture geometry on permeability; their study results concluded that increased fracture orientation would exponentially increase permeability. Namdari et al [17] investigated the effect of the discontinuity direction on fluid flow in porous rock masses; they used a hybrid FVM-DFN and streamline simulation approach. The study results indicated that the FVM-DFN hybrid method is effective if it uses the streamlined simulation to study the fluid flow in a large model with discontinuity.…”
Section: Introductionmentioning
confidence: 99%
“…Faez et al [16] studied the effect of fracture geometry on permeability; their study results concluded that increased fracture orientation would exponentially increase permeability. Namdari et al [17] investigated the effect of the discontinuity direction on fluid flow in porous rock masses; they used a hybrid FVM-DFN and streamline simulation approach. The study results indicated that the FVM-DFN hybrid method is effective if it uses the streamlined simulation to study the fluid flow in a large model with discontinuity.…”
Section: Introductionmentioning
confidence: 99%
“…The streamline simulation is one of the most feasible methods for dominant flow characterization. In recent years, streamline simulation has attracted more and more attention (Mesbah et al, 2019;Wang et al, 2020;Morse and Mahesh, 2021;Namdari et al, 2021;Zhang et al, 2021). However, discrete streamline distribution cannot accurately represent the actual flow field, limiting its effective application to the oil field.…”
Section: Introductionmentioning
confidence: 99%